Eksistensi Akal sebagai Epistemologi dalam Merasionalkan Wahyu Pada Perspektif Islam Rasional Harun Nasution (W-1998) - Rizal Lubis; Syukri Syukri (Moderasi : Journal of Islamic Studies, 2026)
This study aims to analyze the role of reason as an epistemological framework in rationalizing revelation from the perspective of Harun Nasution’s rational Islam. This study is motivated by the importance of the relationship between reason and revelation in understanding Islamic teachings amid the development of science and modernity. This study employs a qualitative method using a literature review (library research) approach. Data were obtained from the works of Harun Nasution and related literature, then analyzed using content analysis. This study is limited to a literature review of Harun Nasution’s thought. The results are expected to enrich the study of Islamic epistemology, particularly regarding the integration of reason and revelation in the development of contemporary Islamic thought. The results indicate that Harun Nasution regards reason as a crucial instrument in understanding and interpreting revelation. According to him, reason and revelation share a harmonious relationship; revelation serves as the source of absolute truth, while reason functions to explain and implement the values of revelation in daily life. The rational use of reason does not diminish the sanctity of revelation but rather strengthens the relevance of Islamic teachings to the changing times. The originality of this study lies in its focus on the epistemological function of reason in rationalizing revelation according to Harun Nasution, thereby contributing to the development of critical, open, and moderate Islamic thought.